The Impact of Social Support on Job Satisfaction Among Precast Concrete Workers in Indonesia: A Cross-Sectional Study - Rizka Lailatul Rohmah; Baiduri Widanarko (International Journal Of Health Science, 2025)
The construction sector in Indonesia plays a vital role in economic development but is also characterized by high rates of workplace accidents, informality, and job insecurity. These challenges may negatively affect workers’ well-being and job satisfaction, especially in demanding environments such as precast concrete manufacturing. Social support has been recognized as a key psychosocial factor that can improve workplace outcomes, yet little is known about its role in Indonesia’s construction workforce. This study aims to (1) examine the level of perceived social support among precast concrete workers, (2) assess their level of job satisfaction, and (3) analyze the relationship between social support and job satisfaction. A cross-sectional design was employed, involving 180 workers from three precast concrete plants in Java, selected through random sampling. Data were collected using the Indonesian versions of the Job Content Questionnaire (JCQ) and Copenhagen Psychosocial Questionnaire II (COPSOQ II), and analyzed using logistic regression. The results revealed that 76.7% of workers reported low social support, and 72.8% experienced low job satisfaction. Workers with high social support were significantly more likely to report high job satisfaction (OR = 6.985; 95% CI: 3.276–14.895). These findings confirm that social support is a strong predictor of job satisfaction in this population. Strengthening support from supervisors and coworkers may be a strategic intervention to improve worker well-being and retention in Indonesia’s construction industry.